2021
DOI: 10.3390/cells10092228
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Leucine Zipper-Mediated TLR2 Downregulation Accounts for Reduced Neutrophil Activity Following Acute DEX Treatment

Abstract: Glucocorticoids are the most powerful anti-inflammatory and immunosuppressive pharmacological drugs available, despite their adverse effects. Glucocorticoid-induced leucine zipper (GILZ) is a glucocorticoid-induced gene that shares several anti-inflammatory properties with glucocorticoids. Although immunosuppressive effects of glucocorticoids on neutrophils remain poorly understood, we previously demonstrated that GILZ suppresses neutrophil activation under glucocorticoid treatment. Here, we sought to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Based on our previous detection of increased neutrophil in ltration in the lungs of DKO pups 19 , we sought to analyze whether DEX or NAC antenatal treatment had some effect on lung neutrophil extravasation in these animals. As expected, dexamethasone, a glucocorticoid able to inhibit the immune response 33,34 , produced a complete reversion of neutrophil in ltration in the DKO lungs (Fig. DEX and NAC treatments restore the normal bronchiolar cell architecture in the neonatal DKO lungs Given our previous observations showing a signi cant morphological alteration ( attening) of Club cells (HRas and NRas single and double-KO) and Ciliated cells (only in DKO lungs) 19 , we wished to compare here the structure of these bronchiolar cell lineages in P0 mice before and after receiving antenatal DEX or NAC treatments (Fig.…”
Section: Neutrophil In Ltration Decreases After Antenatal Dex or Nac ...supporting
confidence: 79%
“…Based on our previous detection of increased neutrophil in ltration in the lungs of DKO pups 19 , we sought to analyze whether DEX or NAC antenatal treatment had some effect on lung neutrophil extravasation in these animals. As expected, dexamethasone, a glucocorticoid able to inhibit the immune response 33,34 , produced a complete reversion of neutrophil in ltration in the DKO lungs (Fig. DEX and NAC treatments restore the normal bronchiolar cell architecture in the neonatal DKO lungs Given our previous observations showing a signi cant morphological alteration ( attening) of Club cells (HRas and NRas single and double-KO) and Ciliated cells (only in DKO lungs) 19 , we wished to compare here the structure of these bronchiolar cell lineages in P0 mice before and after receiving antenatal DEX or NAC treatments (Fig.…”
Section: Neutrophil In Ltration Decreases After Antenatal Dex or Nac ...supporting
confidence: 79%
“…Additionally, long-term treatments with some efficacious drugs, such as glucocorticoids and other immunosuppressants, lead to serious adverse effects, including metabolic alterations and increased risk of infections and malignancies (55,56). GILZ is a protein that mediates several anti-inflammatory effects of glucocorticoids, and previous studies on GILZp have reported promising results for the treatment of IBD (6,8,(57)(58)(59)(60). Considering that GILZ is also involved in the pathophysiology of IBD, as demonstrated in both preclinical models of colitis and in patients, in this study, we investigated the effects of combining GILZp with a potential prebiotic yeast extract (Py) in a mouse model of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of glucocorticoids (GCs) on the regulation of TLR2 expression remains a subject of discussion. Findings from various studies have reported conflicting outcomes, with some indicating downregulation and others suggesting upregulation of TLR2 ( Hoppstädter et al, 2019 ; Ricci et al, 2021 ). Moreover, genetic variations in TLRs have been associated with variations in the severity of leptospirosis.…”
Section: Gcs Tlrs and Leptospira Infectionmentioning
confidence: 99%